Nuclei in motion: movement and positioning of plant nuclei in development, signaling, symbiosis and disease. - Anna Hare Newman Griffis; Norman Reid Groves; Xiao eZhou; Iris eMeier (Frontiers in Plant Science, 2014)
While textbook figures imply nuclei as resting spheres at the center of idealized cells, this picture fits few real situations. Plant nuclei come in many shapes and sizes, and can be actively transported within the cell. In several contexts, this nuclear movement is tightly coupled to a developmental program, the response to an abiotic signal, or a cellular reprogramming during either mutualistic or parasitic plant-microbe interactions. While many such phenomena have been observed and carefully described, the underlying molecular mechanism and the functional significance of the nuclear movement are typically unknown. Here, we survey recent as well as older literature to provide a concise starting point for applying contemporary molecular, genetic and biochemical approaches to this fascinating, yet poorly understood phenomenon.